Development of Diagnostic, Formative and Summative Assessment Instruments in the PjBL Model to Strengthen the Profile of Pancasila Physics Students - Marjuni; Festiyed (Postgraduate, University of Mataram, 2024)
This research has two purposes. The first is to develop a diagnostic, formative and summative assessment tool using the Project Based Learning (PjBL) model to strengthen the profile of Pancasila physics students. The second is to examine the validity and usability of the developed assessment tool. The first objective outcome is the product of assessment tools in the form of activity and assessment sheets. The outcome of the second objective is to obtain a valid and practical assessment tool that strengthens the student profile of Pancasila. The conclusion from the development of this tool is that the tool developed in the form of activity and assessment pages is practical and suitable for use in the classroom to strengthen the profile of Pancasila physics students.